INFLUENCE OF CEO OVER CONFIDENCE, GENDER DIVERSITY AND PROFITABILITY ON CORPORATE TAX AVOIDANCE: EMPIRICAL STUDY ON MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Giri Darijanto Sugiono; Yolanda Anggraeny (Bina Nusantara University, 2022)
This research aims to determine the influence of individual and company characteristics on tax avoidance by examining and analyzing the impact of CEO overconfidence, gender diversity, and profitability on corporate tax avoidance. The rationale of this research is that there is still a lack of research, the authors identify the relationship between CEO overconfidence, gender diversity, and profitability using tax avoidance measurement, i.e., cash effective tax rate (CETR) followed by control variables of sales growth and capital intensity. This study used secondary data with entire manufacturing companies listed on Indonesia Stock Exchange for 2017-2019. The sample was determined using the purposive sampling method and obtained 96 samples. The analysis method used in this research is panel data regression with corporate tax avoidance as the dependent variable and CEO overconfidence, gender diversity, and profitability as independent variables. This research indicates that profitability positively affects corporate tax avoidance, while CEO overconfidence and gender diversity have no significant effect on corporate tax avoidance.